2006
DOI: 10.1097/01.mpa.0000202949.64870.87
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Trophic Pancreatic Effects in Humans With Long-term Administration of Ximelagatran

Abstract: In contrast to rats, in which long-term oral administration of ximelagatran stimulates pancreatic growth and adenoma formation, in humans, ximelagatran does not increase plasma CCK concentrations and has no demonstrable trophic effect on the human pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In another study from the same group, the mTOR pathway was shown to be essential for camostat-induced pancreatic growth through the use of rapamycin, a selective mTOR inhibitor [57 ]. The effects of another oral trypsin inhibitor, ximelagatran, were analyzed in humans but no increase in plasma CCK or pancreatic size was found [58]. This can be explained by the fact that in humans, unlike in rodents, CCK levels only increase when elastase and chymotrypsin as well as trypsin are inhibited.…”
Section: Regulation Of Pancreatic Protein Synthesis and Growthmentioning
confidence: 96%
“…In another study from the same group, the mTOR pathway was shown to be essential for camostat-induced pancreatic growth through the use of rapamycin, a selective mTOR inhibitor [57 ]. The effects of another oral trypsin inhibitor, ximelagatran, were analyzed in humans but no increase in plasma CCK or pancreatic size was found [58]. This can be explained by the fact that in humans, unlike in rodents, CCK levels only increase when elastase and chymotrypsin as well as trypsin are inhibited.…”
Section: Regulation Of Pancreatic Protein Synthesis and Growthmentioning
confidence: 96%
“…In the rat, CCK1 receptor but not CCK2 receptor agonists increased pancreatic mass by increasing the number of cells comprising the exocrine pancreas (72). Since the human pancreas lacks CCK1 receptors, administration of ximelagatran, which has protease inhibitor activity and stimulates pancreatic growth in rats, did not have a significant effect on pancreatic growth in humans (56). Despite the lack of hypertrophic effects observed in human studies, it was recently shown that pancreatic atrophy resulting from total parenteral nutrition (TPN) could be reversed by CCK in rodents.…”
Section: Trophic Effect Of Cck On the Pancreasmentioning
confidence: 95%
“…CCK secretion is under the control of negative feedback regulation by pancreatic proteases and bile acids (25,56,70). In most species, including humans, it has been shown that food-stimulated CCK secretion is suppressed by release of pancreatic proteases (31,34,54).…”
Section: Regulation Of Cck Secretionmentioning
confidence: 99%
“…Recently, imaging studies using CT or MRI have been used and give similar values for pancreatic size in humans to earlier autopsy studies (72,99,119,126). A study in pigs validated the method by comparing the pancreatic volume obtained by MRI to water displacement after pancreas removal (141).…”
Section: Measurement Of Pancreatic Sizementioning
confidence: 99%